THE IMPACT OF SUBSIDY POLICY FOR COMPETITIVENESS OF PADDY FARMING IN GORONTALO PROVINCE, INDONESIA - Zulkifli Mantau; Nuhfil Hanani; M Muslich Mustajab; S Syafrial (Agricultural Socio-Economics Journal, 2019)
Abstract: The aims of this research are 1) to analyze the policy impact of input and output subsidies to paddy-rice competitiveness, and 2) to analyze the comparative and competitive advantages of paddy farming in Gorontalo Province, Indonesia. The research conducted at Gorontalo Province. The method use Policy Analysis Matrix (PAM) to measure the competitiveness parameters such a Domestic Resources Cost Ratio (DRCR) as a ratio for comparative advantages and Private Cost Ratio (PCR) as a ratio for competitive advantages. Meanwhile, PAM also measure the protection coefficients, such a Nominal Protection Coefficient on Output and Input (NPCO and NPCI), Effective Protection Coefficient (EPC). In additional, Producer Subsidy Equivalent (PSE) was used to measure a relative incentive for producers (farmers). Consumer Subsidy Equivalent (CSE) was used to measure a relative incentive for consumer. The results showed that NPCO and NPCI are 1.35 (there’s government protection for output/ rice) and 0.42 (there’s protection for inputs or subsidies for tradable inputs), respectively. The result of the EPC is 1.51. EPC> 1 indicates that government protection works effectively to rice commodity. Based on PAM analysis, PCR and DRCR values in this study were 1.14 and 1.52, respectively. PSE obtained value of 0.33 which indicate that producers (farmers) are not receiving direct or indirect incentives from government subsidy policies. CSE obtained results -0.27 at the level of actual prices and -0.37 at the border price. It indicates that consumers lost a surplus of 27% of the domestic rice price on average, or 37% of the border price.